A Thiazolothiazole-Based Semiconducting Polymer with Well-Balanced Hole and Electron Mobilities - Masahiko Saito; Itaru Osaka (Applied Sciences, 2019)
We report the synthesis and properties of a new thiazolothiazole (TzTz)-based semiconducting polymer incorporating the dithienothienothiophenebisimide (TBI) unit, named PTzTBI. PTzTBI showed relatively deep HOMO and LUMO energy levels of −5.48 and −3.20 eV, respectively. Although PTzTBI mainly formed face-on backbone orientation unfavorable for transistors, PTzTBI functioned as an ambipolar semiconductor for the first time with TzTz-based polymers, with reasonably high and well-balanced hole (0.02 cm2 V−1 s−1) and electron (0.01 cm2 V−1 s−1) mobilities.